Pengoptimalan E-Learning di SMA Kyai Ageng Basyariah Madiun melalui Pelatihan Google Classroom - Vera Dewi Susanti; Tri Andari (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
To overcome the spread of covid 19, schools and universities conduct learning through online activities. In online learning, the Kyai Ageng Basyariyah high school teacher still uses WhatsApp only, so learning is not optimal. This is less effective so that more meaningful learning training is needed such as Google Classroom training as one of the innovations in online learning. This training begins with pre-training preparations such as licensing, module preparation, and training support equipment. Then direct training was held, namely an explanation of the introduction of Google Classroom and hands-on practice which was attended by 23 teachers. The results of the practice of training activities using the Google Classroom application for the online learning process at SMA Kyai Ageng Basyariyah have been carried out well and smoothly and show that the training participants have mastered how to use Google Classroom.